1999
DOI: 10.1098/rsta.1999.0326
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic cavitation: the fluid dynamics of non–spherical bubbles

Abstract: In acoustic cavitation the spatial variation and time-dependent nature of the acoustic pressure field, whether it is a standing or propagating wave, together with the presence of other bubbles, particles and boundaries produces gradients and asymmetries in the flow field. This will inevitably lead to non-spherical bubble behaviour, often of short duration, before break-up into smaller bubbles which may act as nuclei for the generation of further bubbles. During the collapse phase, high temperatures and pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
75
0
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(84 citation statements)
references
References 34 publications
5
75
0
4
Order By: Relevance
“…In addition, multibubble applications always have to deal with the interaction of bubbles with boundaries, be they hard (as in materials science) or soft (as in biological and medical contexts). With the experimental observation and numerical simulation of jet cavitation in bubble collapses near a wall by Lauterborn (1988a, 1988b), Vogel et al (1989), Tomita and Shima (1990), Blake et al (1997), Philipp and Lauterborn (1997), Lauterborn and Ohl (1998), Blake et al (1998Blake et al ( , 1999, Tong et al (1999), Brujan et al (2001aBrujan et al ( , 2001b, research in this complex area has only just begun.…”
Section: E Multibubble Fields: In Search Of a Theorymentioning
confidence: 99%
“…In addition, multibubble applications always have to deal with the interaction of bubbles with boundaries, be they hard (as in materials science) or soft (as in biological and medical contexts). With the experimental observation and numerical simulation of jet cavitation in bubble collapses near a wall by Lauterborn (1988a, 1988b), Vogel et al (1989), Tomita and Shima (1990), Blake et al (1997), Philipp and Lauterborn (1997), Lauterborn and Ohl (1998), Blake et al (1998Blake et al ( , 1999, Tong et al (1999), Brujan et al (2001aBrujan et al ( , 2001b, research in this complex area has only just begun.…”
Section: E Multibubble Fields: In Search Of a Theorymentioning
confidence: 99%
“…In addition, we study power intensities above those that have been reported by others. [7][8][9] This paper reports new findings in terms of energy balance and intense power densities for the production of biodiesel with ultrasonics.…”
Section: Introductionmentioning
confidence: 99%
“…6 The effect of ultrasonic waves on liquids has been discussed in detail by Suslick. 7 Others have explained non-spherical cavitation, 8 while more recently, some have studied multiphysical models involving ultrasonics and biodiesel production. 9 Peshkovsky et al reported the cavitation produced from shock waves, which may have relevance to the work presented in this study.…”
Section: Introductionmentioning
confidence: 99%
“…wave scattering effects [26,27], damping mechanisms [29][30][31][32], bubble instability [33,34] and wave propagation in bubbly mediums [35,36]. For example, the wave speed in bubbly mediums is a strong function of both frequencies and bubble sizes as shown in Figures 6 and 7.…”
Section: Other Effectsmentioning
confidence: 89%